Comparison of Volar Locking Plate and Percutaneous Pinning Using the Faisal Technique for Volar Barton Fractures: Faisal Technique for Volar Barton Fractures - Aslam, Shoaib; Ali, Muhammad Asjad; Saqlain, Syed Salman; Asif, Hafiz Salman; Aslam, Hafiz Muhammad Asad; Iqbal, Muhammad; Hameed, Sajid (Pakistan Journal of Health Sciences, 2025)
Volar plates are employed for buttressing volar fragments in most situations, and even dorsal fragments are stabilized by this technique. K-wires are often preferred. Objective: To compare the frequency of excellent outcomes in volar Barton fractures of the distal radius managed with open reduction and internal fixation using volar plates versus percutaneous pinning by the Faisal technique. Methods: A total of 60 patients with volar Barton fractures, aged 20 to 70 years of both genders, were included. Patients with bilateral fractures, recurrent fractures on the same side, open fractures, wrist dislocations, arthritic wrists, neurovascular injury, and Chauffeur’s fractures were excluded. In Group A, a volar plate was implanted. In Group B, percutaneous pinning using K-wires was performed. After 3 months, patients were evaluated for functional outcomes using the Green O’Brien Scoring System. Results: The mean age of patients in Group B was 42.37 ± 15.23 years, and in Group A was 42.33 ± 14.04 years. The majority of patients, 31 (51.67%), were between 20 to 45 years of age. Of the 60 patients, 47 (78.33%) were male and 13 (21.67%) were female, with a male-to-female ratio of 3.6:1. An excellent outcome was observed in 24 (80.0%) patients in Group B and 11 (36.67%) patients in Group A, with a p-value of 0.001. Conclusion: This study concluded that the frequency of excellent outcomes in volar Barton fractures of the distal radius was significantly higher with percutaneous pinning by the Faisal technique compared to volar plate fixation.